The Location of Emergency Service Facilities - Toregas, Constantine; Swain, Ralph; ReVelle, Charles; Bergman, Lawrence (Operations Research, 1971)
This paper views the location of emergency facilities as a set covering problem with equal costs in the objective. The sets are composed of the potential facility points within a specified time or distance of each demand point. One constraint is written for each demand point requiring “cover,” and linear programming is applied to solve the covering problem, a single-cut constraint being added as necessary to resolve fractional solutions.